Study of the correlation between indoor air quality in school buildings and children’s health problems in Greece (International Journal of Occupational Safety and Health, 2026)
Introduction: In the last years, air quality studies are focused  on the indoor environments of the school buildings, since children spend much of their daily time in the classrooms. There is proof  that indoor air pollutants can cause health problems to the vulnerable school population. The purpose of this study was to examine the correlation between air quality in school classrooms and students’ health.Methods: The study was conducted in sixty-one (61) classrooms of thirty-three (33) school buildings located in the Central Athens within the Attica Region and in the Argolida Sector of the Peloponnese Region in Greece. Students’  health  who attended  the selected school classrooms was evaluated by anonymous questionnaires completed  by the students’ parents. Indoor concentrations of chemical air pollutants in the selected classrooms such as carbon dioxide (CO2), carbon  monoxide (CO), volatile organic compounds (VOCs), nitrogen dioxide (NO2), particulate matters (PM10, PM2.5), along with temperature (T) and relative humidity (RH), were monitored using the series 500 Portable Air Quality Monitor and used for the statistical correlations.Results: Study showed that there was a statistically significant correlation between indoor CO2 (p=0.007) and students’ performance, indoor VOCs (p=0.023), PM2.5 (p=0.008) and bronchitis, indoor PM2.5 (p=0.002) and asthma, indoor PM10 (p=0.002), PM2.5 (p=0.012)  and migraines in students.Conclusion: Indoor air pollutants were related with students’ health problems. Indoor air quality in school buildings is a very serious environmental issue and authorities must enforce health policy strategies in order to minimize air pollutant concentrations in classrooms and protect student  health.